2017
DOI: 10.1080/2326263x.2017.1307625
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic applications of BCI technologies

Abstract: Brain-computer interface (BCI) technology can restore communication and control to people who are severely paralyzed. There has been speculation that this technology might also be useful for a variety of diverse therapeutic applications. This survey considers possible ways that BCI technology can be applied to motor rehabilitation following stroke, Parkinson’s disease, and psychiatric disorders. We consider potential neural signals as well as the design and goals of BCI-based therapeutic applications. These di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
35
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(35 citation statements)
references
References 123 publications
(118 reference statements)
0
35
0
Order By: Relevance
“…In theory, a BCI might contribute to functional recovery in several different ways [5]. Dobkin [48] suggested that practical BCI systems could be used as a tool to reinforce the use of spared neural representations or to insure that subjects were optimally prepared to execute a particular movement.…”
Section: Bcis For Neurorehabilitationmentioning
confidence: 99%
See 1 more Smart Citation
“…In theory, a BCI might contribute to functional recovery in several different ways [5]. Dobkin [48] suggested that practical BCI systems could be used as a tool to reinforce the use of spared neural representations or to insure that subjects were optimally prepared to execute a particular movement.…”
Section: Bcis For Neurorehabilitationmentioning
confidence: 99%
“…To date, these studies have been mainly demonstrations of proof-of-principle: actual long-term BCI use by individuals who need them has been limited to a handful of case studies [e.g., 4]. More recently, investigators have become interested in other applications of BCI technology, particularly the possibility that they might enhance neurorehabilitation for people with strokes and other chronic disorders [5]. …”
Section: Introductionmentioning
confidence: 99%
“…The first paper summarizes the 28 workshops; the next three papers provide detailed reports from three of them. One addresses the emerging therapeutic applications of BCIs [6]; the next is a detailed discussion of the advances made in BCIs for stroke rehabilitation [7]. Both review work in which a BCI aids recovery from disabling conditions, sometimes producing long-term effects that persist after BCI use is discontinued.…”
mentioning
confidence: 99%
“…Of great interest is the SMR, these rhythms are observed as a decrease in the activity in the Alpha band (8)(9)(10)(11)(12) and Beta band (16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26) when the subject executes motor task. Interestingly the decrease in the power in the frequencies mentioned before is also observed when the subject imagines the movement, which is of especial interest in applications for people with degenerative diseases.…”
Section: Introductionmentioning
confidence: 99%
“…BCI systems are aimed to population who suffer from motor disabilities, making use of different phenomena present in the brain activity [1,2,3,4,5,6,7,8,9,10] . However, the application of BCI is not restricted only to rehabilitation.…”
Section: Introductionmentioning
confidence: 99%